LABORATORY TESTING OF LEICA AT401 LASER TRACKER - Filip Dvořáček (Acta Polytechnica, 2016)
This paper describes laboratory tests on a Leica AT401laser tracker. As the newer Leica AT402 model also uses the same firmware package, most of the results should also be valid for this device. First, we present the instrument’s firmware errors and the software used for testing. The ASME B89.4.19-2006 standard for testing laser trackers is briefly presented. The warm-up effect of the instrument is inspected with respect to both angle measurement and distance measurement. The absolute distance meter (ADM) is compared with a laboratory interferometer on a 30-meter long rail and also on a bench with automated movement of the carriage of the reflector. A time series of measurements for determining the additive constant is evaluated. A simple test of the stability of the distance measurement in field conditions is introduced. Most of the tests were carried out at the Research Institute of Geodesy, Topography and Cartography (RIGTC) and at the Faculty of Civil Engineering (FCE) of the Czech Technical University in Prague (CTU).